Human skeletal muscle fiber type percentage and area after reduced muscle use: A systematic review and meta-analysis - Vikne, H.; Strøm, V.; Pripp, A. H.; Gjøvaag, T. (Scandinavian Journal of Medicine & Science in Sports, 2020)
The main objective of this systematic review was to examine the effect of reduced muscle activity on the relative number of type 1 muscle fibers (%) in the human vastus lateralis muscle. Other objectives were changes in type 2A and 2X percentages and muscle fiber cross-sectional area. We conducted systematic literature searches in eight databases and included studies assessing type 1 fiber percentage visualized by ATPase or immunohistochemical staining before and after a period (=14 days) of reduced muscle activity. The reduced muscle activity models were detraining, leg unloading, and bed rest. Forty-two studies comprising 451 participants were included. Effect sizes were calculated as the mean difference between baseline and follow-up and Generic Inverse Variance tests with random-effects models were used for the weighted summary effect size. Overall, the mean type 1 muscle fiber percentage was significantly reduced after interventions (-1.94%-points, 95% CI [-3.37, -0.51], P = .008), with no significant differences between intervention models (P = .86). Meta-regression showed no effect of study duration on type 1 fiber percentage (P = .98). Conversely, the overall type 2X fiber percentage increased after reduced muscle activity (P < .001). The CSA of the muscle fiber types decreased after the study period (all P-values < 0.001) with greater reductions in type 2 than type 1 fibers (P < .001). The result of this meta-analysis display that the type 1 muscle fiber percentage decrease as a result of reduced muscle activity, although the effect size is relatively small.